The Eschar Size and Early Inoculation Lesion of Tsutsugamushi Disease on Jeju Island, Korea - Kim, Young Hoon (Infect Chemother, 2019)
BACKGROUND: Tsutsugamushi disease, or scrub typhus, is an acute febrile illness caused by Orientia tsutsugamushi, which is followed by chronic latent infection. People who reside in areas endemic of tsutsugamushi disease may be frequently reinfected with this organism. Volunteers who are experimentally reinfected with O. tsutsugamushi manifest various systemic and local reactions, including the presence of small-sized eschar. The present study recorded the morphology and size of eschars in patients with tsutsugamushi disease on Jeju Island, Korea. MATERIALS AND METHODS: From March 2018 to February 2019, 23 patients manifesting clinical characteristics and epidemiologic features of tsutsugamushi disease on Jeju Island were investigated. For comparison of eschar sizes between the two regions, 12 patients with tsutsugamushi disease in Incheon were similarly examined. RESULTS: Three patients, two on the first day and one on the fourth day of fever, presented with papules of 2 – 5 mm in diameter. Another three patients, one on the second day and two on the fourth day, presented with ruptured vesicles of 5 – 8 mm in diameter. Thirteen patients presented with eschars covered with dark scabs, with a median diameter of 5 (95% confidence interval [CI], 5 – 7.5) × 4 (95% CI, 3 – 5) mm. The medians of the eschar sizes did not differ between the two cities (P = 0.46 by Mann-Whitney U test), but eschars ≥10 mm in diameter were more frequent in Incheon than in Seogwipo-si (4 of 12 vs. 0 of 13 patients, P = 0.04 by Fisher's exact test). One patient presented with multiple eschars, and no eschar was detected in the remaining three patients. Among 11 Jeju Island patients with positive IgG and IgM antibodies, seven patients revealed higher IgG than IgM antibody titers during the acute phase of the illness, i.e., the IgG antibody response, two patients had equal IgG and IgM titers, and two patients presented the IgM antibody response. Life-threatening complications and death were not observed in this study. CONCLUSION: The patients in Seogwipo-si had small-sized eschars and occasionally exhibited non-necrotic lesions. Many patients had serologically reinfected tsutsugamushi disease. Further studies are needed to investigate the association between these findings.